(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Development of the method of evaluating the effectiveness of ocular adnexa (OA) traumatic injuries treatment will allow determining the efficiency of the different treatment methods. Purpose is to develop the method of evaluating the effectiveness of ocular adnexa traumatic injuries treatment. Materials and methods. The study was conducted in 120 patients with ocular adnexa traumas. Patients were randomized in two representative groups by age and sex of 60 patients according to the reconstructive procedures methods. The results were evaluated in early and late postoperative period by proposed comprehensive system for ocular adnexa status evaluation using modern statistical methods. Results and discussion. The degree of ptosis, lagophthalmos, eyelids malposition, lacrimal patency, presence of scarring, deformities and cosmetic defects were taking into consideration in the evaluation of the ocular adnexa traumatic injuries treatment effectiveness. All indices were estimated in numerical score system. The result of ocular adnexa traumatic injuries treatment considered good when the index was from 7 to 11, satisfactory – from 12 to 16, unsatisfactory – from 17 to 20 scores according to the proposed scale. Conclusions. The use of the proposed method enables to compare the results of different methods of reconstructive procedures along with determination of the ophthalmosurgery effectiveness in patients with ocular adnexa traumatic injuries.